CAPACITY ANALYSIS SECONDARY ROAD BASED ON CONNECTION OF TRAFFIC FLOW, SPEED AND DENSITY ON MEDAN CITY - Wirdatun Nafiah Putri; Muhammad Mabrur; Tetra Oktaviani (Program Studi Teknik Sipil, Fakultas Teknik. Universitas Samudra, 2021)
Transportation infrastructure planning that was not carried out properly causes road disruption in urban areas. Jl. Balaikota, Jl. Putri Hijau, Jl. Yos Sudarso and Jl. Willem Iskandar are the network secondary road in the city of Medan, which is a diversion route for the main traffic flow transportation from and to the city to reduce primary arterial road burdens and traffic density in the city. Indicators to road traffic performance in order to understanding traffic behavior are vehicle speed, density, and traffic volume. Direct observation surveys were conducted to collect speed and traffic volume datas. The density value is obtained from the relationship between the two parameters. The Greenshield, Greenberg and Underwood result model are the maximum volume, density and speed that can be accommodated by the road segment are obtained, then linear regression analysis is carried out to select the appropriate model for the road conditions. Models for Jl. City Hall and Jl. Yos Sudarso Section 2 is Greenshield Model, Jl. Putri Hijau, Jalan Yos Sudarso Section 1 and Jl. Willem Iskandar is a Greenberg Model. Jalan Balaikota has a maximum traffic volume of 3808.40 pcu/hour, a density of 248.53 pcu/km, Jl. Putri Hijau 5107.40 pcu/hour with a density of 312.62 pcu/km, Jl. Yos Sudarso Section 1 of 1627 pcu/hour with a density of 109.17 pcu/km, Jl. Willem Iskandar Section 1 of 2897.80 pcu/hour with a density of 146.84 pcu/km and Jl. Willem Iskandar Section 2 1304.60 pcu/hour with a density of 76.28 pcu/km